Exploring rural youth livelihood opportunities: a case study of a youth centre in Bizana - Mtwa, Zikhona Asanda (Rhodes University, Faculty of Humanities, Department of Sociology)
Throughout South Africa, youth that are not in Education, Employment, or Training (NEET) continue to face many socio-economic challenges, including unemployment. Bizana, a small rural town in the Eastern Cape, is no exception. This study explores rural youth livelihood opportunities for youth NEET in Bizana. There is limited research done to understand the role of youth centres in providing accessing to rural youth livelihood opportunities. As a result, this study sought to understand the role of youth centres in re-integrating youth NEET into the labour market, as well as into education and training institutions. It utilizes the case study of the Bizana Love Life youth centre by looking at the programmes they offer, and whether they enhance livelihood opportunities for youth NEET. The Sustainable Livelihoods Approach (SLA) was used as a theoretical lens in understanding rural youth livelihood opportunities for youth NEET in Bizana, by identifying the challenges they face and the assets they use to enhance their livelihoods. Against this backdrop, the study adopted a qualitative research approach and an explorative case study design and was supplemented by purposive and snowball sampling methods. Data was obtained using semi-structured interviews with twelve youth NEET participants who are part of the programmes of the youth centre, and two staff members of the youth centre. Findings were analysed using open coding and thematic analysis in line with the objectives of the study. The findings of the study revealed that in attempting to gain employment, extended family support, parenthood, financial reasons, household chores, poor academic performance and lack of work experience were some of the challenges facing rural youth NEET in Bizana. The findings indicate that a combination of human and social capital can be used to support youth NEET in gaining confidence and in preparing them for the workplace. With these findings, the study indicates the need to strengthen existing youth programmes that cater for youth NEET, who are the most vulnerable in the labour market, through skills development and broadening of their social networks. As a policy recommendation, the national and provincial government must work with youth centres and other stakeholders to establish policies that cater for the development of youth NEET.
Keywords: Rural youth -- South Africa Bizana; Youth centers -- South Africa Bizana; Sustainable livelihood; NEET